Activation of Group II Metabotropic Glutamate Receptors Inhibits Glutamatergic Transmission in the Rat Entorhinal Cortex via Reduction of Glutamate Release Probability - Wang, Shouping (Oxford University Press, 2012)
Glutamate interacts with ionotropic and metabotropic glutamate receptors (mGluRs). Whereas the entorhinal cortex (EC) is a principal structure involved in learning and memory, the roles of mGluRs in synaptic transmission in the EC have not been completely determined. Here, we show that activation of group II mGluRs (mGluR II) induced robust depression of glutamatergic transmission in the EC. The mGluR II–induced depression was due to a selective reduction of presynaptic release probability without alterations of the quantal size and the number of release sites. The mechanisms underlying mGluR II–mediated suppression of glutamate release included the inhibition of presynaptic release machinery and the depression of presynaptic P/Q-type Ca(2+) channels. Whereas mGluR II–induced depression required the function of Gα(i/o) proteins, protein kinase A (PKA) pathway was only involved in mGluR II–mediated inhibition of release machinery and thereby partially required for mGluR II–induced inhibition of glutamate release. Presynaptic stimulation at 5 Hz for 10 min also induced depression of glutamatergic transmission via activation of presynaptic mGluR II suggesting an endogenous role for mGluR II in modulating glutamatergic transmission.